Symmetry position/force hybrid control for cooperative object transportation using multiple humanoid robots. (17th January 2016) - Wu, Meng-Hung; Ogawa, Shuhei; Konno, Atsushi
Abstract : A symmetry position/force hybrid control framework for cooperative object transportation tasks with multiple humanoid robots is proposed in this paper. In a leader-follower type cooperation, follower robots plan their biped gaits based on the forces generated at their hands after a leader robot moves. Therefore, if the leader robot moves fast (rapidly pulls or pushes the carried object), some of the follower humanoid robots may lose their balance and fall down. The symmetry type cooperation discussed in this paper solves this problem because it enables all humanoid robots to move synchronously. The proposed framework is verified by dynamic simulations. Graphical Abstract: